C57BL/6 and Swiss Webster Mice Display Differences in Mobility, Gliosis, Microcavity Formation and Lesion Volume After Severe Spinal Cord Injury - Noristani, Harun Najib; They, Laetitia; Perrin, Florence Evelyne (Frontiers in Cellular Neuroscience, 2018)
Spinal cord injuries (SCI) are neuropathologies causing enormous physical and emotional anguish as well as irreversibly disabilities with great socio/economic burdens to our society. The availability of multiple mouse strains is important for studying the underlying pathophysiological response after SCI. Although strain differences have been shown to directly affect spontaneous functional recovery following incomplete SCI, its influence after complete lesion of the spinal cord is unclear. To study the influence of mouse strain on recovery after severe SCI, we first carried out behavioral analyses up to 6 weeks following complete transection of the spinal cord in mice with two different genetic backgrounds namely, C57BL/6 and Swiss Webster. Using immunohistochemistry, we then analyzed glial cell reactivity not only at different time-points after injury but also at different distances from the lesion epicenter. Behavioral assessments using CatWalk™ and open field analyses revealed increased mobility (measured using average speed) and differential forelimb gross sensory response in Swiss Webster compared to C57BL/6 mice after complete transection of the spinal cord. Comprehensive histological assessment revealed elevated microglia/macrophage reactivity and a moderate increase in astrogliosis in Swiss Webster that was associated with reduced microcavity formation and reduced lesion volume after spinal cord transection compared to C57BL/6 mice. Our results thus suggest that increased mobility correlates with enhanced gliosis and better tissue protection after complete transection of the spinal cord.